Wireless Power Transmission via Modulated Laser Irradiation of Pyroelectric Thin Films. Issue 9 (18th October 2016) - Hanrahan, Brendan; Neville, Cameron; Smith, Andrew; Ter‐Gabrielyan, Nikolay; Jankowski, Nicholas; Waits, Chris Mike
Abstract : Long‐distance wireless power transmission is enabled by laser‐heating a pyroelectric thin film. The modulated laser is synchronized with an applied electric field in order to accomplish energy conversion cycles. Energy density is found to vary with synchronization while power density is optimized by the trade‐off between laser power and the transient thermal properties of the thin film system.